Pengembangan Media Audio Visual Layanan Klasikal Bidang Karir pada Materi Orientasi Masa Depan di SMA Srijaya Negara Palembang - Islamiati, Tri Septiana; Sofah, Rahmi; Harlina, Harlina (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2019)
This type of research is development research by using the ADDIE model. This research aimed to produce products of audio visual media which were valid, practical and effective. The research was conducted at SMA Srijaya Negara Palembang. This research consisted of 5 stages, namely 1) analysis (pre-test and interview with BK teacher), 2) design (making RPL and media manuscript), 3) development (making media, after the media was finished, the researcher conducted validation with three experts: material expert, media expert, language expert and small group test), 4) implementation (field test and post-test), 5) evaluation (strengths and limitations of the media). The results obtained at pretest with materials that can be updated in the future are 47.9% in the